2001
DOI: 10.1161/01.cir.103.4.532
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Late Clinical Outcomes of Carotid Artery Stenting in Patients With Symptomatic and Asymptomatic Carotid Artery Stenosis

Abstract: Experience from a single group of operators demonstrates that carotid stenting can be performed with an acceptable 30-day complication rate. Late follow-up also demonstrates a low rate of fatal and nonfatal stroke. These results suggest that carotid stenting may be comparable to carotid endarterectomy, and it underscores the clinical equipoise and premise for the National Institute of Health-supported, randomized Carotid Revascularization Endarterectomy Versus Stent Trial comparing carotid stenting with caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
314
0
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(337 citation statements)
references
References 29 publications
8
314
0
10
Order By: Relevance
“…Os benefícios da endarterectomia em pacientes sintomáticos com estenose entre 50 e 69% no NASCET, ECST e outros foram claramente menores do que naqueles com estenose maior [32][33][34][35] . Assim, nesse grupo, a endarterectomia tem maior valor para aqueles com alto risco de acidente vascular cerebral, como nos homens com 75 anos ou mais, sintomas hemisféricos e acidente vascular cerebral há 3 meses ou menos 1 .…”
Section: E Tab Iii)unclassified
See 1 more Smart Citation
“…Os benefícios da endarterectomia em pacientes sintomáticos com estenose entre 50 e 69% no NASCET, ECST e outros foram claramente menores do que naqueles com estenose maior [32][33][34][35] . Assim, nesse grupo, a endarterectomia tem maior valor para aqueles com alto risco de acidente vascular cerebral, como nos homens com 75 anos ou mais, sintomas hemisféricos e acidente vascular cerebral há 3 meses ou menos 1 .…”
Section: E Tab Iii)unclassified
“…34 acompanharam 528 pacientes submetidos a angioplastia com stent por cinco anos e seus resultados sugeriram que o procedimento pode ser comparável à endarterectomia.…”
Section: E Tab Iii)unclassified
“…9 Of special note are the success and complication rates of carotid artery stenting that have been observed with the development of the technique. As reported by Roubin et al, 10 success rates of 98% are now achievable, and the incidence of minor strokes seems to be declining. What does not seem to be declining, however, is the incidence of procedure-related major stroke.…”
Section: See P 12mentioning
confidence: 72%
“…found that patients ≥80 years old had a 16% stroke rate in comparison to 5.4% in young patients, and thought that old age (≥80)had a negative influence on periprocedural adverse events Roubin et al. (2001). The lead‐in phase of the CREST trial showed that the periprocedural risk of stroke and death after CAS increased with age and was 12.1% in patients aged over 80, significantly above the rates for patients aged 70–79 (5.3%), 60–69 (1.3%), and less than 60 (1.7%) (Hobson et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that after the periprocedural period, the majority of elderly patients are free from cerebrovascular complications. These results are also concordant with a previous large registry data, which demonstrated that, in patients who survive the periprocedural period, freedom from fatal and nonfatal ipsilateral stroke was 99% at 3 years (Roubin et al., 2001). In our study, we explain the lower rates of stroke and death by the fact that we excluded patients with significant medical comorbidities such as abnormal creatine clearance, hemoglobin level and cancer, and by the frequent follow‐ups we conducted to ensure no new conditions arose.…”
Section: Discussionmentioning
confidence: 99%